Immunodeficiencies and genetic mutations affecting NK cells in humans - Orange, Jordan (Henry Stewart Talks, 2009)
NK cell deficiency, Critical role of NK cells in human host defense, Recognition of NK cell deficiencies in the context of other genetic human immunodeficiency, Phenotypes of isolated NK cell deficiencies, Insights into basic NK cell biology and immunity from experiments of nature